IMPLEMENTASI KEBIJAKAN PENGELOLAAN BANTUAN OPERASIONAL PENDIDIKAN PESANTREN PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI GORONTALO - Jaura K Yanji; Arifin Tahir; Fenti Prihatini Dance Tui (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to discover (1) the implementation of the policy in managing operational assistance for islamic boarding schools at the Regional Office of the Ministry Of Religios Affairs of Gorontalo Province, (2) the determinants of the policy implementation in managing operational assistance for islamic boarding school at the Regional Office of the Ministry of Religios Affairs of Gorontalo Province in terms of its communication, resources, disposition and bureaucratic structure, Furthermore, this study uses a qualitative approach with a descriptive method, wheres the data collection is conducted using observation, interviews and documentation. Based on the study results, (1) the process of managing operational assistance for Islamic boarding schools at the Regional Office of the Ministry of Religious Affairs of Gorontalo Province, encompassing aspects of planning, implementation, evaluation and monitoring have been carried out properly. However, several Islamic boarding schools do not meet the requirements, such as not having an IZOP (operational license), the will to access SIMBA (Assistance Management Information System) aplication, and the requirements, in proposing a proposal or a budget plan. Moreover, (2) the determinants of the policy implementation in managing operational assistance for Islamic boarding schools, in the aspect of communication, resources, disposition and bureaucratic structure, have been carried out as well as possible, However, according, to the available resources, Islamic boarding schools remain inadequate. For instance, the operators of Islamic boarding schools have not been able to control and apply SIMBA application and it primarily causes by network contraints and server maintenance.Â